The Possibilities of Additive Manufacturing in Medical Use - Szabó, Dániel (International Journal of Engineering and Management Sciences, 2019)
Additive Manufacturing has been invented in 1981 at the University of Texas, and to this day it has grown to be the most versatile and promising manufacturing technology in the market, both the industry and health care system has noticed this. Additive Bio-Manufacturing (ABM) techniques, which can be used in health care, are highly in demand, and researches have been going on to make these technologies safer and even more versatile. For more utilization and versatility, special attention is required to develop new materials which can help in increasing the service life, bioactivity, cell growth along with the desired mechanical properties, and to find the right manufacturing parameters for creating optimal products. The aim of this review is to present the available main Additive Manufacturing technologies, and particularly the biomedical usability of Additive Manufacturing.